PENERAPAN MODEL BELAJAR INKUIRI UNTUK MENINGKATKAN PRESTASI BELAJAR IPA DALAM MATERI POKOK DAUR HIDUP PADA SISWA KELAS V MI SUNAN KALIJOGO - Nurhaningtyas Agustin; Munthofi’ah (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2019)
Learning is a way for someone to gain knowledge through experience, remembering, and getting information / finding. Teaching through providing experience in finding his own knowledge, it is hoped that these lessons will be meaningful for students. This study aims to find out about the application of inquiry learning models, improve student learning achievement through inquiry models, student responses to the application of inquiry learning models in science subjects the subject matter of life cycle in class V MI Sunan Kalijogo Wolutengah Kerek District, Tuban lesson year 2017/2018. This research is a type of Classroom Action Research (Action Classroom Research). The data in this study are data on increasing the learning achievement of science subjects in the life cycle with inquiry learning models. Data analysis was carried out by observing student activities, questionnaires to determine student responses that were calculated in the form of percentages, and data from student evaluation results. From the implementation of this study the results were obtained (1) that the application of inquiry learning models in science learning the subject matter of the life cycle of living things can improve student learning achievement. The increase can be seen from the learning outcomes achieved by students in the first cycle and second cycle which are significant. (2) student learning achievement has increased after the implementation of inquiry learning models. After the application of the inquiry learning model in the first cycle the average value of students was 62.63, in the second cycle it increased to 81.84. Increased activity of students in observation or group discussion, in the first cycle 52.63%, in the second cycle to 84.21%. The accuracy of completing the chart or table of observation in the first cycle is 57.89%, in the second cycle becomes 84.21%. The activity at presentation in the first cycle was 15.79%, increasing in the second cycle to 57.89%. The intensity of play alone decreased from 31.58% to 15.79% in cycle II. (3) Positive student responses, indicated by 17 students (89.47%) liked the application of the inquiry learning model, and 2 students (10.53%) did not like because they felt left behind from their friends. The results of this class action research can be categorized as successful in its implementation. The conclusions from the results of this study that the application of inquiry learning models in science subjects the subject matter of the life cycle in class V MI Sunan Kalijogo Wolutengah Kerek District, Tuban Regency 2017/2018 school year can improve student learning achievement.